Developing Professionalism and Professional Identity Through Unproctored, Flexible Testing. (April 2019) - Ross, Paula T.; Keeley, Meg G.; Mangrulkar, Rajesh S.; Karani, Reena; Gliatto, Peter; Santen, Sally A.
Abstract : The medical education community has devoted a great deal of attention to the development of professionalism in trainees within the context of clinical training—particularly regarding trainees' handling of ethical dilemmas related to clinical care. The community, however, knows comparatively less about the development of professional behavior in medical students during the preclerkship years. In medical schools with flexible testing, students take quizzes or examinations in an unproctored setting at a time of their choosing—as long as it falls within a specified window of time. Unproctored, flexible testing offers students early opportunities to develop appropriate professional behavior. In this Perspective, the authors outline different flexible testing models from three institutions—University of Virginia School of Medicine, University of Michigan Medical School, and Icahn School of Medicine at Mount Sinai—all of which offer various levels of testing flexibility in relation to time and location. The authors' experiences with these models suggest that preclinical medical students' early development of professional behavior requires scaffolding by faculty and staff. Scaffolding involves setting clear, specific expectations for students (often through the form of an honor code), as well as active engagement and discussion with learners about the expectations and procedures for self-regulation in the academic environment.